2006
DOI: 10.21236/ada603511
|View full text |Cite
|
Sign up to set email alerts
|

Reduced PM2.5 Emissions for Military Gas Turbine Engines using Fuel Additives

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Table 3 shows a compilation of the latest as well as significant kerosene surrogates from the literature, the number of species and reactions in their respective reaction mechanisms, as well as the target properties that each surrogate was made to emulate. 45,51,56,6870,82,85,154156,158,161,163186…”
Section: Development Of Kerosene Surrogates Their Chemical Reaction Mechanisms and The Modeling Of Kerosene Combustion In Dici Enginesmentioning
confidence: 99%
“…Table 3 shows a compilation of the latest as well as significant kerosene surrogates from the literature, the number of species and reactions in their respective reaction mechanisms, as well as the target properties that each surrogate was made to emulate. 45,51,56,6870,82,85,154156,158,161,163186…”
Section: Development Of Kerosene Surrogates Their Chemical Reaction Mechanisms and The Modeling Of Kerosene Combustion In Dici Enginesmentioning
confidence: 99%
“…Moreover, researchers have determined that different physical properties of aviation fuels will affect combustion performance as well as soot formation. Roquemore and Litzinger found that blended fuel with high initial and end boiling points can contribute to high particle numbers. Calcote and Manos defined an equation of a threshold sooting index (TSI) to rate the soot formation tendency based on smoke point and molecular weight of the fuel.…”
Section: Introductionmentioning
confidence: 99%